Climate, carbon content, and soil texture control the independent formation and persistence of particulate and mineral-associated organic matter in soil - Haddix, Michelle L.; Gregorich, Edward G.; Helgason, Bobbi L.; Janzen, Henry; Ellert, Benjamin H.; Francesca Cotrufo, M. (Geoderma, 2020)
•After six months litter C was found in all soil fractions.•Similar amounts of litter C in the mineral fraction at six months and five years.•Sand content and precipitation best predict litter C formed in mineral fraction.•We found a positive feedback between new litter-derived SOM and soil C content. Understanding the mechanisms controlling the formation and persistence of soil organic matter (SOM) is important for managing soil health and sustainable food production. The formation of SOM and the degree to which it is protected from decomposition are important for determining the long-term persistence of SOM. We used soils collected in a 13C-labelled litter decomposition study established at agricultural sites in Canada to understand the formation and persistence of newly-formed SOM. The ten agricultural sites spanned a wide range of soil carbon contents, texture, and climatic conditions. We fractionated the soil to isolate water extractable organic matter (WEOM), free light POM (fPOM), sand-sized and occluded particulate organic matter (oPOM), and silt and clay sized particles, referred to as mineral-associated organic matter (MAOM). Quantitative isotope tracing was used to determine the litter-derived C in all fractions. We performed these analyses early (six months after incubation) and later (five years after incubation) in the decomposition process to evaluate factors that control the formation and persistence of POM and MAOM. After six months litter-derived C was found in all fractions, but after five years it had declined in all fractions except the MAOM. Formation of MAOM was related to high mean annual precipitation and low sand content, whereas occluded POM formation was related to high soil C content. Persistence of MAOM and POM during the incubation were associated with low soil temperature and high soil C content. There was no consistent indication that formation of MAOM occurred from the decomposition of POM, suggesting that MAOM and POM are formed by two separate pathways. This has important implications for SOC models, which assume that plant-derived C passes through a sequence of pools, becoming more stable along the way.